Eurasian guidelines for the diagnosis and treatment of pulmonary hypertension associated with congenital heart defects in adults (2021) - I. E. Chazova; S. V. Gorbachevskij; T. V. Martynyuk; A. A. Shmal’c; Z. S. Valieva; I. Yu. Baryshnikova; L. A. Glushko; V. V. Gramovich; V. A. Azizov; T. N. Veselova; N. M. Danilov; P. A. Zelveyan; et al. (Евразийский Кардиологический Журнал, 2022)
.